Synthesis, Spectroscopic and Semiempirical Studies of New Quaternary Alkylammonium Conjugates of Sterols - Brycki, Bogumił (Molecules, 2013)
New quaternary alkylammonium conjugates of steroids were obtained by two step reaction of sterols (ergosterol, cholesterol, dihydrocholesterol) with bromoacetic acid bromide, followed by bimolecular nucleophilic substitution with a long chain tertiary alkylamine. The structures of products were confirmed by spectral ((1)H-NMR, (13)C-NMR, and FT-IR) analysis, mass spectrometry and PM5 semiempirical methods. The pharmacotherapeutic potential of synthesized compounds has been estimated on the basis of Prediction of Activity Spectra for Substances (PASS).